2012
DOI: 10.1080/15428052.2012.650603
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Extracurricular Foodservice Work Experience on Culinary Graduate Industry Experience

Abstract: This purpose of this article is to examine the influence of extracurricular foodservice work experience on the foodservice industry persistence of culinary graduates. The researcher used a survey methodology to obtain experiential data from culinary graduates. Post facto data from school records were used to enrich the survey data and provide an opportunity to observe the potential influence of extracurricular foodservice employment on in-school performance. A novel survey instrument was developed and validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Many studies have shown that there are a number of factors that influence job satisfaction. Mesch (2012) found that graduates with higher educational grades had higher industry persistence scores. Mesch (2012) also found that moderate levels of extra curricular food service experience during schooling appeared to be a benefit to graduates, who had greater industry persistence, which was linked to job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that there are a number of factors that influence job satisfaction. Mesch (2012) found that graduates with higher educational grades had higher industry persistence scores. Mesch (2012) also found that moderate levels of extra curricular food service experience during schooling appeared to be a benefit to graduates, who had greater industry persistence, which was linked to job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Many culinary schools are rethinking their culinary curriculum in line with developments in media, science and technology. A number of researchers have highlighted the need for further research into the effectiveness and content of culinary education Müller et al, 2009;Mesch, 2012;Shani et al, 2013;Magnusson Sporre et al, 2015). There are a number of planned Culinary Arts Degree programmes currently being developed in Canada, Australia and New Zealand.…”
Section: Educationmentioning
confidence: 99%
“…Bu açıdan bakıldığında Türkiye'deki gastronomi ve mutfak sanatları programlarının amacının da aşçılık programları gibi nitelikli "mutfak elemanı" yetiştirmek olduğu düşünülebilir ancak konu ile ilgili yapılan araştırmaların yetersizliği ve eğitimini başarı ile tamamlayan mezunlara verilecek unvan konusunda Yükseköğretim Kurulu Başkanlığı'nın (YÖK) bir kararı bulunmaması (Özdemir, 2017) ilgili programların turizm fakültesi (n=24), uygulamalı bilimler yüksekokulu (n=11), turizm ve otelcilik yüksekokulu (n=4), güzel sanatlar-sanat ve tasarım fakültesi (n=17) gibi farklı fakülte ve yüksekokullarda açılması (Yökatlas, 2018) bölümün misyonunun ne olduğu konusunda şüphe uyandırmakta, programların amacı ve gastronomi algısında belirsizliğe neden olmaktadır. Uluslararası literatür (Brown, 2005;Brown, Mao & Chesser, 2013;Cheng, vd., 2011;Harrington, Mandabach, Thibodeaux & Vanleeuwen, 2005;Hertzman, 2008;Hertzman & Stefanelli, 2008;La Lopa, 2009;Maberly & Reid, 2014;Mesch, 2012;Wollin & Gravas, 2001;Yen, Cooper & Murrmann, 2013;Zopiatis, Theodosiou & Constanti, 2014) (Brough, 2008, s. 70). Bu nedenle çalışmanın ilerleyen bölümleri mutfak eğitimi yeterliğini etkileyen faktörler ekseninde şekillenmiştir.…”
Section: Kavramsal çErçeveunclassified
“…Lisans programının niteliğini büyük ölçüde uygulanan müfredat belirler. Uluslararası literatür (Brough, 2008;Brown, 2005;Harrington, Mandabach, Thibodeaux & Vanleeuwen, 2005;Hertzman, 2008;Hertzman & Maas, 2012;Mesch, 2012;Wollin & Gravas, 2001) incelendiğinde Brough, 2008, s. 373, 385;Hertzman, 2008). Brough'a (2008) (Brown, 2005, s. 52).…”
Section: İlişkin Değerlendirmelerunclassified
“…Research on chefs is underrepresented in the hospitality literature. Historical research on chefs and restaurants has increased in recent years (Davis, 2013;Mac Con Iomaire, 2013Mennell, 1996;Spang, 2000). Sociological research on chefs began with Whyte's (1948) study of Chicago restaurants.…”
Section: Literature Reviewmentioning
confidence: 99%